Phytochemical screening expedition 2009 : drug discovery from nature. - Mat So'ad, Siti Zaiton; Mohd Hassan, Norazian; Khamis, Shamsul (IIUM Press, 2011)
Malaysia is a tropical country endowed with very rich and diverse specIes of flora with promising medicinal values, which are still fully untapped, The country also has a strong tradition in ethnomedical practices, many ohvhich utilize the local flora. These two factors have initiated the research in natural products sciences, which provide an ideal common ground for collaboration between chemists, botanists and pharmacologists. In addition, phytochemical research on our local medicinal plants is an area of great potential that needs to be explored further. For that reason, Phytochemical Screening Expedition has been regularly organized as yearly programme at Kulliyyah ofPharmacy since 2009